Pengembangan PAI Berbasis Pendidikan Karakter - Mukhlisin, Nurul (Ali Muchasan, 2015)
Our education (as one of the important elements in educating the nation's generation must be properly managed in order to improve the morals of the nation. This is because the essence of education is actually not just teaching (transfer of knowledge), but more than that is to educate to morals. Through Islamic Education, learners are expected to have these characters This paper will try to explain how the development of character-oriented Islamic Education development with several studies, namely philosophical bases, character education theories, national character development model and Islamic religious education, Implications and application of Character education model. To optimize the implementation of character education, it must get support from all parties, especially teachers and parents who have a very important role. They are a vibrant curriculum, exemplary and passionate to educate learners must exist within teachers and parents. Therefore, the educator must be characterized before forming the character of learners, so that learners can absorb and apply for what is instilled by educators.